An econometric analysis of the determinants of fertility : International evidence / Wun Kim Yen, Ratneswary Rasiah and Jason James Turner - Wun, Kim Yen; Rasiah, Ratneswary; Turner, Jason James (Universiti Teknologi MARA, 2018)
This study aims to analyse the socio and macroeconomic determinants of fertility in 108 countries across the globe. Focusing on the variables of inflation, income, education level and urbanization, this study employs the cross-sectional econometrics technique of Ordinary Least Squares to analyse the causal relationship between these variables and fertility. The empirical results reveal a significant and negative relationship between income and fertility in the overall model of the 108 countries, as well as in the models involving developing countries, and countries in the African, American and Asian regions. Education was found to also have a significant and negative relationship with fertility in the overall model and the developing countries. Urbanisation, on the other hand, was found to have a significant and positive relationship with fertility in the overall model, developing countries and in countries in the African and Asian regions. Inflation was the only predictor found to be not significant in all the models. As far as the least developed countries, developed countries and the countries in the European region were concerned, none of the independent variables were significant predictors of fertility. The study concludes with an examination of policy implications of the findings